Self-harm in relation to attachment theory and the cry of pain model: attachment insecurities and feelings of entrapment as vulnerability factors - Cuenca, Jose (2013)
Self-harm thoughts and behaviour have been found to be associated with a wide variety of distal and proximal factors; however, few studies have examined how these factors work together to increase the risk of self-harm. A key distal factor is a history of child and family adversity, which attachment theory views as a precursor of attachment insecurities that may increase the risk of later self-harm. A key proximal factor is the desire to escape from overwhelming distress, and Williams (2001) cry of pain model describes a process that could help better understand the reasons behind seeking escape via self-harm. This research investigated whether insecurely attached individuals tend to feel trapped and whether entrapment leads to self-harm thoughts (suicide ideation [Chapter 2] and thoughts about non-suicidal self-injury [Chapter 3]). This research also investigated whether feelings of entrapment among insecurely attached individuals varied as a function of problem-solving (as assessed with the Means-Ends Problem-Solving [MEPS] procedure [Chapter 4] and a diary study [Chapter 5]). The effect of stressful events on subsequent feelings of defeat and entrapment, and the role of attachment, was also examined using an experimental design (Chapter 6).